Estrategias discursivas de exclusión hacia la población migrante en los foros televisivos: estudio comparativo de dos casos - Rojas, Diego Noel Ramos (Comparative Cultural Studies: European and Latin American Perspectives, 2019)
This work shows how some statements that claim validity and orientation to understanding are also discursive strategies used to represent, through video analysis forums, migrants who travel to the United States as a dangerous group that must be controlled. The theoretical perspective is the critical analysis of discourse and a methodology was used based on the classification of speech acts of Austin and Habermas and the model of the types of representations of social actors of Leeuwen. The results show that migrants are represented as depersonalized subjects, excluded, without the right to participate in decision making and inserted in a process of otherness.